Optimasi Perencanaan Produksi dengan Multiobjective: Implementasi Model Goal Programming - Aulia, Olif; Nuha, Hilyatun; Murnawan, Hery (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Industrial development in the era of globalization requires companies to be able to carry out optimal production planning in order to compete in the market. UD Anugerah Abadi is a company engaged in the garment sector located in Surabaya. The company produces Muslim koko shirts used by adults. UD Anugerah Abadi as one of the medium-scale industry players faces challenges in determining the amount of production in accordance with market demand, limited raw materials, and production capacity. Based on preliminary observations, it is known that the production planning system at UD Anugerah Abadi is still manual and intuitive, with a simple approach so that there are often discrepancies between the amount of production and actual demand, especially UD Anugerah Abadi experiences instability in demand for clothing production, this instability can be caused by economic conditions, many competitors with similar products, and so on. Therefore, to be able to solve production problems at UD Anugerah Abadi, researchers want to conduct research related to the Development of the Goal Programming Model on Production Planning Optimization at UD Anugerah Abadi. The formulation of the problem in this study is how to determine the forecasting method and Goal Programming optimization model that will be used for production at UD Anugerah Abadi, with the research objectives of understanding and knowing the forecasting method and Goal Programming optimization model that will be used for production at UD Anugerah Abadi.